Effect of a Multimodal Movement Intervention in Patients With Neurogenic Claudication Based on Lumbar Spinal Stenosis and/or Degenerative Spondylolisthesis—A Pilot Study - Broscheid, Kim-Charline; Behrendt, Tom; Hamacher, Dennis; Böker, Svantje; Gagelmann, Tabea; Schmidt, Christian; Caspari, Christina; Meiler, Katharina; Napiontek, Andre; Franke, Jörg; Schega, Lutz (Frontiers in Medicine, 2020)
Chronic low-back pain is a major individual, social and economic burden. The impairment ranges from deterioration of gait, limited mobility to psychosocial distress. Due to this complexity, the demand for multimodal treatments is huge. Our purpose is to compare the effects of a multimodal movement intervention (MI) (coordinative-cognitive exercises and dancing program) with standard Physical Therapy (PT) on gait, physical function and quality of life in patients with lumbar spinal stenosis (LSS). The study design is based on a six-week intervention with a two (group: MI/PT) by two (measurement time points: pre-/post-test) parallel group design with random assignment. Twenty-four subjects (18 female/6 male, 70.8±10.6 years old) diagnosed with LSS were included and randomly allocated to the MI or PT group. The primary outcomes are Minimum Toe Clearance (MTC) and Double Step Length (DSL) variability and the Timed “Up & Go” test (TUG). Secondary outcomes are the Brief Pain Inventory, the short Fall Efficacy Scale-International (sFES-I) and the Oswestry Disability Index. Nine subjects for each group could be analysed. The MTC variability revealed a significant between-group difference in the post-test (p=.008) showing a lower MTC variability for the MI compared to the PT group. The MI group displayed an improved TUG (p=.031) and a reduced sFES-I (p=.044). The decreased MTC variability and fear of falling as well as the improved functional mobility may contribute to a reduced risk of falling. For the subsequent study, further kinematic and cognitive parameters should be analyzed, and the number of participants has to be increased.